2022
DOI: 10.2215/cjn.16751221
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles as Theranostic Tools in Kidney Disease

Abstract: Extracellular vesicles are important vectors for cell-cell communication and show potential value for diagnosis and treatment of kidney diseases. The pathologic diagnosis of kidney diseases relies on kidney biopsy, whereas collection of extracellular vesicles from urine or circulating blood may constitute a less invasive diagnostic tool. In particular, urinary extracellular vesicles released mainly from resident kidney cells might provide an alternative tool for detection of kidney injury. Because extracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 120 publications
1
10
0
Order By: Relevance
“…EVs from different types of stem cells, their routes of administration and also mechanism of actions have been studied [2]. Very recently uEVs have been found to be protective in a glycerol induced AKI model, in which Klotho might serve a function in regeneration [56](for review see [57], [2], [6], [58]).…”
Section: Evs In Aki and Transition To Ckdmentioning
confidence: 99%
See 3 more Smart Citations
“…EVs from different types of stem cells, their routes of administration and also mechanism of actions have been studied [2]. Very recently uEVs have been found to be protective in a glycerol induced AKI model, in which Klotho might serve a function in regeneration [56](for review see [57], [2], [6], [58]).…”
Section: Evs In Aki and Transition To Ckdmentioning
confidence: 99%
“…EVs from different types of stem cells, their routes of administration, and also mechanism of actions have been studied. 2 Very recently uEVs have been found to be protective in a glycerol-induced AKI model, in which Klotho might serve a function in regeneration 72 (for review, see 2,7,8,73 ). Significant progress has been made to understand the regenerative role of EVs in AKI and CKD, but still many challenges exist to understand the EV types and optimal techniques in isolation, storage, and preparation to guarantee safety and minimize possible long-term side effects of EV therapeutics in AKI.…”
Section: Evs In Aki and Transition To Ckdmentioning
confidence: 99%
See 2 more Smart Citations
“…To decrease and ultimately overcome the issue of variability among uEV studies, guidelines for reporting on isolation, characterization, and normalization have been developed by EV-TRACK (evtrack.org) and the Urinary Task Force of the International Society for Extracellular Vesicles [1,12]. Recent reviews have covered uEV biomarkers in other kidney diseases and kidney transplantation as well the therapeutic use of EVs [13,14]. Here, we review which tubular transporters have been identified and characterized in uEVs, how EVs may regulate tubular transporters, and whether uEV cargo may reveal disease mechanisms and serve as biomarkers for kidney disease and hypertension.…”
Section: Introductionmentioning
confidence: 99%